New governance and management in touristic destinations - Valeri, Marco (Advances in hospitality, tourism, and the services industry book series., 2022)
"This book offers new insights for traditional paradigms, approaches and methods, as well as more recent developments in research methodology in new approaches to governance and management of destination, outlining how and why tourist destinations have to act more like businesses than they have done in the past"--